Alcohol Addiction and Cognitive Function among Café Visitors at South Jakarta - Andrew Suwadi; Dharmady Agus; Stefanus Lembar (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Alcohol addiction has an acute and chronic impact, and may cause cognitive function impairment, in the form of interference in decision making and impulse control, as well as impaired motor function. Furthermore, research on alcohol addiction and cognitive function has not been widely studied in Indonesia. The purpose of this study was to explore the association between alcohol addiction and cognitive function among café visitors at South Jakarta. Methods: This was a cross sectional study, conducted among cafévisitors at South Jakarta in 2018. The respondents of this study were individuals who have consumed alcohol in the last 12 months and not consumed narcotics, psychotropic, and other addictive substances except nicotine and caffeine. Alcohol addiction among respondent was assessed by the CAGE questionnaire and cognitive function was assessed by the MoCA-Ina questionnaire. Statistical analysis was determined by Chi Square test.Results: In total, 80 respondents consisting of 57 men and 23 women met the study criteria, 67.5% of respondents have experienced alcohol addiction and 85.2% have experienced poor cognitive function. There was a strong association between alcohol addiction and cognitive function among café visitors (p=0.000; OR=44.083).Conclusions: Individual with alcohol addiction has a poor cognitive function compared with people without alcohol addiction. Therefore, awareness of the adverse effects of alcohol addiction on cognitive function among community is needed and thus, people are expected to distance from alcohol addiction.